PAIN MANAGEMENT IN CHILDREN WITH CANCER: CONTRIBUTIONS TO NURSING - Patrícia Curti Bueno; Eliane Tatsch Neves; Angelita Gastaldo Rigon (Universidade Federal do Paraná, 2011)
This qualitative, descriptive, retrospective research aimed to describe how Nursing manages pain in children with cancer. The data were collected from the hospital notes of children hospitalised in a unit specialising in the treatment of cancer in a teaching hospital in South Brazil between May and June 2008. The quantitative data were submitted to descriptive analysis and the nursing notes were organised in a synoptic chart to which thematic analysis was applied. The results showed that 47.27% of children presented complaints of pain. Treatment with medicines was the principal response to all and any manifestations of crying; less invasive, or alternative strategies of pain management were rare. It was concluded that there is a need to establish methods for assessment and management of pain, according to the age group and level of development of the child, and to keep nursing notes with attention, allying technical-scientific knowledge with sensitivity and affection.